Measurement and Modeling of Longitudinal Dispersivity in Undisturbed Saturated Soil: An Experimental Approach. Issue 5 (13th September 2018) - Chakraborty, Poulamee; Das, Bhabani Sankar
Abstract : Core Ideas: An experimental procedure is reported to estimate the tortuosity and longitudinal dispersivity values in the same intact soil core. The dimensionless parameter (longitudinal dispersivity upon scale of measurement) is modelled as a function of tortuosity values. The relationship between tortuosity and dispersivity is porous media dependent. The dispersivity (λ) values of soil are extensively modeled as a function of the scale of measurement ( L s ). The relationship between estimated tortuosity (τ) and longitudinal dispersivity (λL ) for intact soil, however, is not reported. Since both τ and λL are properties of the porous media, we reported the relationship between them in this study. The λL was estimated from laboratory scale transport experiments using undisturbed soil spheres with τ ranging from 1.07 to 3.05. The dimensionless parameter λL / L s follows a logarithmic relationship with τ ( R 2 = 0.87). Since λL is a function of both the geometry of the porous media and the microscopic variation of pore velocity, our result for the first time shows the nature of relationship between pore geometry (as captured by τ) and λL values. Such relationships may be built into flow and transport models to have an initial estimate of the dispersivities in soil.